Correlation between degeneration of cervical intervertebral disc and degeneration of paravertebral muscle - Li, Qiujiang; Long, Xingxia; Wang, Rui; Niu, Pengying; Cai, Lijun; Wang, Lei; Song, Yueming (Frontiers in Endocrinology, 2024)
Objective To investigate the relationship between degeneration of cervical intervertebral disc and degeneration of paravertebral muscles[multifidus (MF), cervical semispinalis (SCer), semispinalis capitis (SCap) and splenius capitis (SPL)]. Methods 82 patients with chronic neck pain were randomly selected, including 43 males and 39 females, with 50.73 0.7.51 years old. All patients were scanned by 3.0T MRI Philips Ingenia performed conventional MRI sequence scanning and fat measurement sequence mDIXON-Quant scanning of cervical. Fat infiltration (FI) and cross-sectional area (CSA) of cervical paravertebral muscle (MF, SCer, SCap and SPL) at central level of C5–6 disc were measured by Philips 3.0T MRI image post-processing workstation. According to Pfirrmann grading system, there was no grade I in the included cases. The number of grade IIr IV cases were n=16, 40, 19 and 7 respectively. CSA and FI of cervical paravertebral muscles were compared with t test or one-way ANOVA, Spearman correlation analysis was used to evaluate the correlation between age, disc degeneration, and CSA, FI of cervical paravertebral muscles, and multiple linear regression analysis was used to analyze the independent influencing factors of CSA and FI. Results CSA of cervical paravertebral muscles in male patients was significantly higher than that in female patients (all P<0.001), but there was no significant difference in FI (all P>0.05). Age was weakly correlated with CSA of MF+SCer, moderately correlated with CSA of SCap and SPL (r=-0.256, -0.355 and -0.361, P<0.05), weakly correlated with FI of SCap and SPL (r= 0.182 and 0.264, P<0.001), moderately correlated with FI of MF+SCer (r=0.408, P<0.001). There were significant differences in FI with disc degeneration (P<0.001, P=0.028 and P=0.005). Further correlation analysis showed that disc degeneration was strongly correlated with FI of MF+SCer (r=0.629, P<0.001), and moderately correlated with FI of SCap and SPL (r=0.363, P=0.001; r=0.345, P=0.002). Multiple linear regression analysis showed that sex and age were the influencing factors of CSA of SCap and SPL, sex was the independent influencing factor of CSA of MF+SCer, and disc degeneration was the independent influencing factor of FI. Conclusions Age is negatively correlated with CSA and positively correlated with FI. Disc degeneration was correlated with FI of paravertebral muscles, especially with FI of MF and SCer. Sex and age were the influencing factors of CSA, while disc degeneration was the independent influencing factor of FI.